Variants in CPT1A, FADS1, and FADS2 are associated with higher levels of estimated plasma and erythrocyte delta-5 desaturases in Alaskan Eskimos - Voruganti, V.; Higgins, P.; Ebbesson, S.; Kennish, J.; Göring, H.; Haack, K.; Laston, S.; Drigalenko, E.; Wenger, C.; Harris, W.; Fabsitz, R.; Devereux, R.; et al. (2012)
The delta-5 and delta-6 desaturases (D5D and D6D), encoded by fatty acid desaturase 1 (FADS1) and 2 (FADS2) genes, respectively, are rate-limiting enzymes in the metabolism of ω-3 and ω-6 fatty acids. The objective of this study was to identify genes influencing variation in estimated D5D and D6D activities in plasma and erythrocytes in Alaskan Eskimos (n = 761) participating in the genetics of coronary artery disease in Alaska Natives (GOCADAN) study. Desaturase activity was estimated by product: precursor ratio of polyunsaturated fatty acids. We found evidence of linkage for estimated erythrocyte D5D (eD5D) on chromosome 11q12-q13 (logarithm of odds score = 3.5). The confidence interval contains candidate genes FADS1, FADS2, 7-dehydrocholesterol reductase (DHCR7), and carnitine palmitoyl transferase 1 A, liver (CPT1A). Measured genotype analysis found association between CPT1A, FADS1, and FADS2 single-nucleotide polymorphisms (SNPs) and estimated eD5D activity (p-values between 10-28 and 10-5). A Bayesian quantitative trait nucleotide analysis showed thatrs3019594 in CPT1A, rs174541 in FADS1, and rs174568 in FADS2 had posterior probabilities > 0.8, thereby demonstrating significant statistical support for a functional effect on eD5D activity. Highly significant associations of FADS1, FADS2, and CPT1A transcripts with their respective SNPs (p-values between 1075 and 17) in Mexican Americans of the San Antonio Family Heart Study corroborated our results. These findings strongly suggest a functional role for FADS1, FADS2, and CPT1A SNPs in the variation in eD5D activity.